2006
DOI: 10.1002/jts.20131
|View full text |Cite
|
Sign up to set email alerts
|

Subjective distress from stressful events and high-risk behaviors as predictors of PTSD symptom severity in clients with severe mental illness

Abstract: Survey data collected from 257 community mental health center clients tested direct and indirect relationships among subjective distress associated with stressful/traumatic events and high-risk behaviors, substance abuse, and posttraumatic stress disorder (PTSD) symptoms. Structural equation modeling (SEM) revealed substantial direct effects of subjective distress associated with lifetime physical and sexual abuse on PTSD symptom severity. Subjective distress related to high-risk behaviors (e.g., suicide attem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 46 publications
1
54
0
1
Order By: Relevance
“…Perhaps the difference is due to the inhibitory role of dissociation (i.e., blocking painful affect), mental avoidance, or memory problems in clients with schizophrenia (Read et al 2003;Lysaker et al 2005). Differences could also be related to high rates of co-morbidity between PTSD and MMD in SMI samples (Mueser et al 1998;O'Hare et al 2006), a factor that might compound grief symptoms in people with mood disorders when compared with those with schizophrenia spectrum disorders. Whichever the case, one should not conclude from these data that people with SSD suffer any less from their losses than do clients with MMD.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Perhaps the difference is due to the inhibitory role of dissociation (i.e., blocking painful affect), mental avoidance, or memory problems in clients with schizophrenia (Read et al 2003;Lysaker et al 2005). Differences could also be related to high rates of co-morbidity between PTSD and MMD in SMI samples (Mueser et al 1998;O'Hare et al 2006), a factor that might compound grief symptoms in people with mood disorders when compared with those with schizophrenia spectrum disorders. Whichever the case, one should not conclude from these data that people with SSD suffer any less from their losses than do clients with MMD.…”
Section: Discussionmentioning
confidence: 93%
“…Perhaps this difference is due to the higher rates of MMD's and interpersonal abuse in women as seen in the current sample, or a general tendency for women to experience greater subjective distress and perceived threat from traumatic events (Olff et al 2007). As some have suggested (O'Hare et al 2006;Shalev 1996) it might be more clinically useful to examine stressful and traumatic events on a continuum of severity, and understand their impact as a function of the client's subjective appraisal of the event, the consequences of which are amplified or attenuated by associated psychosocial risk and resilience factors, in addition to other individual characteristics (e.g., gender) rather than by relying on a priori definitions of what constitutes trauma or by trying to define the impact of certain stressful life events as a discrete form of mental illness. Longitudinal studies of grief reactions in people with and without co-occurring psychopathology could help to resolve these matters.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…schizophreniaspectrum disorders, bipolar disorders, and major depression) (Mueser et al, 1998;O'Hare, Shen, & Sherrer, 2013;O'Hare, Sherrer, & Shen, 2006;O'Hare, Sherrer, Yeaman, & Cutler, 2009, Resnick, Bond, & Mueser, 2003. Research also suggests that posttraumatic stress disorder (PTSD) can complicate the course and severity of SMI and is associated with marked impairment of social functioning, more frequent symptom relapses and hospitalizations, and more high risk behaviors such as self-harm and suicide attempts (Mueser, Rosenberg, Goodman, & Trumbetta, 2002;O'Hare, Shen, & Sherrer, 2010).…”
mentioning
confidence: 96%
“…There are a number of factors related to mood disturbance that might cause or maintain substance abuse, particularly in this population. Some have suggested that this tendency to use substances to cope with negative emotions might be driven by personality traits (Blanchard et al), or a tendency for some clients to appraise stressful or traumatic events more negatively (Olff, Langeland, Draijer, & Gersons, 2007), or experience greater subjective distress from traumatic events or the consequences of high-risk behaviors (O'Hare et al, 2010;O'Hare, Sherrer, & Shen, 2006), problems for which women are at greater risk. However, research has yet to reveal consistent associations between motives to use and choice of general substance type (e.g., sedatives vs. stimulants) in clients with psychiatric disorders in general, many of whom are polysubstance users (e.g., Mueser et al, 1992;O'Hare & Sherrer, 2011).…”
Section: Implications For Comorbidity Theory and Researchmentioning
confidence: 98%